2009
DOI: 10.1597/08-047.1
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Genes for Cleft Lip and/or Palate Based on Breakpoint Analysis of a Balanced Translocation t(9;17)(q32;q12)

Abstract: Objective-Identification of the breakpoints of disease-associated chromosome rearrangements can provide informative clues to a positional cloning approach for genes responsible for inherited diseases. Recently, we found a three-generation Japanese family segregating balanced chromosome translocation t(9;17)(q32;q12). One of the subjects had cleft lip and palate. We examined whether regions near the breakpoint could be associated with cleft lip and/or palate.Methods-We determined the breakpoints involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…Analysis of breakpoints in patients with balanced rearrangements has identified CLPTM1 [Yoshiura et al, 1998], SATB2 [FitzPatrick et al, 2003], SUMO1 [Alkuraya et al, 2006], and FGFR1 [Kim et al, 2005] as candidate genes for CL/P, and implicated 9q and 17q as potential risk loci [Machida et al, 2009]. In contrast, copy number variants (CNVs) and microdeletions are submicroscopic gains or losses of DNA segments ranging from kilobases to megabases.…”
Section: Nonsyndromic Orofacial Cleftsmentioning
confidence: 99%
“…Analysis of breakpoints in patients with balanced rearrangements has identified CLPTM1 [Yoshiura et al, 1998], SATB2 [FitzPatrick et al, 2003], SUMO1 [Alkuraya et al, 2006], and FGFR1 [Kim et al, 2005] as candidate genes for CL/P, and implicated 9q and 17q as potential risk loci [Machida et al, 2009]. In contrast, copy number variants (CNVs) and microdeletions are submicroscopic gains or losses of DNA segments ranging from kilobases to megabases.…”
Section: Nonsyndromic Orofacial Cleftsmentioning
confidence: 99%
“…We read recently an excellent paper by Machida et al (2009). We were deeply impressed by this very up-to-date and enlighting paper related to genes of cleft lip and cleft palate.…”
mentioning
confidence: 99%
“…In this paper, Machida et al demonstrated that two genes, SLC31A1 (solute carrier family 31 member 1) on chromosome 9 and CCL2 (chemokine ligand 2) on chromosome 17, were rearranged with the breaks occurring within their introns. SLC31A1 lies close to BSPRY (B-box and SPRYdomain), which is a candidate gene for involvement with cleft lip and/or palate (Machida et al, 2009).…”
mentioning
confidence: 99%
“…Os rearranjos genômicos são causados por recombinação imprópria de cromossomos e incluem deleções, duplicações, translocações, inversões e podem ocorrer dentro ou entre cromossomos. A análise de pontos de quebra em rearranjos equilibrados identificou os genes CLPTM1 (159), SATB2 (198), SUMO1 (199), e FGFR1 (94) como genes candidatos para fenda de lábio com ou sem fenda de palato, e implicou as regiões 9q e 17q como potenciais loci de risco (200).…”
Section: Metodologias Para O Estudo De Flp Isoladaunclassified